Challenges that Obstruct Ghana’s Ability to Attract Foreign Direct Investment (FDI) - Boateng, Collins Jerry; Kwevor, Stephen (Minhaj International Journal of Economics and Organization Sciences, 2022)
Research has been conducted on the accounts of Foreign Direct Investment. Most of these researchers used generic variables and this did not lead them in analyzing the county-specific problems. The generic findings of most researchers about FDI are not a good benchmark for interpreting Foreign Direct Investment in a particular country since continents differ so as the countries. This study examines the following elements whether they are challenges facing Ghana in attracting Foreign Direct Investment and these elements are education, taxation policies, political and frequent change of government, infrastructural facilities, inflation, and public debt. However, this study seeks to specifically examine the challenges that impede Ghana’s ability in attracting foreign direct investment and also examine the major areas foreign direct investment is aimed at to curb the challenges or hindrances to improve the economy of Ghana. Foreign direct investment in Africa has been on the rise progressively over the past years and specifically for Ghana hitting a figure of $47.73 million, ranking 3rd in Africa and 1st in central and western Africa. Evidence depicts that foreign direct investment together with production of labor and natural resources brings about advancement or improvement in these targeted areas; technology, acquisition and transfer of knowledge, employment, capital for investment and financial resilience. It is manifested all over the world that foreign investments aids in development of economies and is seen as a strong inducement for socio-economic improvements and if not focused on will no doubts bring about serious challenges faced by the economy of Ghana. On the side of the examined elements, the study found that each element plays vital role in obstructing Ghana’s ability in attracting FDI. Out of the six elements the study found that education, and political and frequent change of government are catalyst in attracting Foreign Direct Investment in Ghana while taxation policies, infrastructural facilities, inflation, and public debt are actually the challenges that impedes Ghana’s ability in attracting Foreign Direct Investment in Ghana. Keywords：FDI, Ghana, Employment, education, taxation policies, political and frequent change of government, infrastructural facilities, inflation, and public debt.